The Impact of Ankylosing Spondylitis in Turkey on Productivity at Work Outside Home and within the Household - Solmaz, Dilek; Cetin, Pinar; Pamuk, Omer Nuri; Cefle, Ayse; Keser, Gokhan; Ozturk, Mehmet Akif; Akkoc, Nurullah (Wiley, 2015)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 06-11, 2015 -- San Francisco, CA